Raising Capital or Improving Risk Management and Efficiency? Key Issues in the Evolution of Regulation and Supervision in European Banks (Springer International Publishing, 2018)
This book analyses the raising of capital imposed by regulatory and supervisory constraints for the soundness and survival of banks in Europe, highlighting critical issues. Accordingly, the text examines the improvement of risk management and efficiency operated by individual banks as the main driver for reinforcing bank resilience and survival. The investigation is carried out essentially through study of risk management, efficiency, capital constraints, bank regulation and supervision in Europe, monetary policy and economic growth in Europe, capital raising in European banks, bank regulation and supervision in the USA, raising of capital or improvement of risk management and efficiency as the final issue. Raising capital by regulatory and supervisory constraints meets solvency requirements at a given time. In contrast, improving risk management and efficiency allows banks to create the best structural premises for reducing costs, increasing revenue and profits and capital level, contributing to the solvency and survival of banks.